2018
DOI: 10.1159/000485463
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Reproducibility of Foveal Avascular Zone Area Measurement on Normal Eyes by Different Optical Coherence Tomography Angiography Instruments

Abstract: Purpose: To compare the foveal avascular zone (FAZ) area measurements produced by different optical coherence tomography angiography (OCTA). Methods: Healthy enrolled volunteers underwent OCTA using 2 different devices: Spectralis HRA+OCTA (Heidelberg Engineering, Heidelberg, Germany) and RS-3000 Advance (Nidek, Gamagori, Japan). Two graders measured FAZ in both superficial (SCP) and deep (DCP) retinal capillary plexuses. The SCP and DCP en face images were visualized automatically segmenting 2 separate slabs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 16 publications
5
20
0
1
Order By: Relevance
“…There are several published reports on repeatability of FAZ size measurement using OCTA in normal eyes with variable findings depending on how FAZ size is measured and what machine is used. [5][6][7][8][9][10] Most studies measured FAZ by segmenting the superficial and/or deep retinal capillary layers separately and showed good repeatability using the same instrument (intra-instrument) but some variability using machines made by different vendors (interinstrument). Repeatability of the FAZ measurement using OCTA in eyes with fundus pathology would be more clinically relevant but has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…There are several published reports on repeatability of FAZ size measurement using OCTA in normal eyes with variable findings depending on how FAZ size is measured and what machine is used. [5][6][7][8][9][10] Most studies measured FAZ by segmenting the superficial and/or deep retinal capillary layers separately and showed good repeatability using the same instrument (intra-instrument) but some variability using machines made by different vendors (interinstrument). Repeatability of the FAZ measurement using OCTA in eyes with fundus pathology would be more clinically relevant but has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high axial resolution, OCTA can visualize multiple layers of micro-retinal vasculature that cannot be analyzed using fluorescein angiography [8]. In addition, OCTA allows detection and measurement of foveal avascular zone (FAZ) area, which can be affected by several retinal diseases [9]. Since the FAZ is surrounded by interconnected capillaries, it is affected by changes in the retinal microvasculature of the macula, which is one of the most important parameters in central retinal circulation [10].…”
mentioning
confidence: 99%
“…The change of the FAZ is critical in many pathological conditions [15][16][17], and the reproducibility of FAZ measurements in the evaluation of the FAZ is important. Previous studies [12,18,19] evaluated the reproducibility of FAZ measurements obtained by different OCTA devices and reported excellent reproducibility and repeatability. However, these results were based on the 3 × 3 mm scan protocols, as few studies have assessed the reproducibility of FAZ measurements obtained by the 6 × 6 mm protocol [7].…”
Section: Discussionmentioning
confidence: 99%
“…Since OCTA is still a relatively new imaging technique, the reproducibility of quantitative metrics obtained by OCTA must be assessed before these data can be confidently interpreted in clinical research and practice. The reproducibility of the FAZ area and macular retinal vasculature measured by different types of OCTA devices have been conducted in some studies [11][12][13]. Corvi et al [10] compared 7 different OCTA devices and found that it was nearly impossible to compare these instruments and that the set of measurements produced by various instruments were not interchangeable.…”
Section: Introductionmentioning
confidence: 99%